High-flux hydrogen irradiation-induced cracking of tungsten reproduced by low-flux plasma exposure. (11th April 2019) - Gao, L.; Manhard, A.; Jacob, W.; von Toussaint, U.; Balden, M.; Schmid, K.
Abstract: Hydrogen-induced cracking (HiC) or blistering is a commonly observed feature in plasma-loaded material surfaces. HiC exhibits a strong dependence on the irradiation parameters, such as incident flux and fluence, particle energy, and sample temperature. However, the underlying physics of this process is still not understood. Focusing on HiC with intragranular cavities in tungsten (W) exposed to deuterium (D) plasma, we apply a one-dimensional (1D) flux-balance model and further propose the crucial role of the solute D distribution in the subsurface region for initiating HiC formation in plasma-loaded surfaces. Within this proposal, HiC features previously observed only under high-flux ( 10 24 D m −2 s −1 ), elevated-temperature ( 500 K) exposure conditions—the coexistence of protrusions with intragranular cavities and small-sized, dome-shaped blisters with intergranular cracking at the surfaces—were reproduced in our low-flux experiments ( 10 20 D m −2 s −1 ) by loading W samples at low sample temperatures (230 K). The presence of protrusions in low-flux experiments is attributed to the comparable local solute D distribution in the corresponding blistering-relevant depth in both types of D plasma exposure. Applying the 1D flux-balance model to the interpretation of HiC formation in plasma-loaded surfaces, the present work allows us to further explore the underlying physics of HiC formation under well-defined experimental conditions.